Bahaya Negatif Penggunaan Hp Bagi Siswa dan Siswi di Lingkungan Smk Raden Rahmat Mojosari - Anam, Muhammad Syafi’i (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The use of mobile phones (HP) among students at SMK Raden Rahmat Mojosari has been increasing along with the development of technology. However, uncontrolled use of mobile phones can have negative impacts on students' development, both academically, socially, and psychologically. This study aims to examine the negative effects of mobile phone use among students at SMK Raden Rahmat Mojosari, focusing on its impact on academic performance, social interaction, and mental health. The research method used is a case study with a qualitative approach. Data were collected through interviews, observations, and literature reviews. The results of the study show that excessive use of mobile phones can disrupt concentration in learning, decrease the quality of social interactions, and increase the risk of mental health issues such as stress and anxiety. Therefore, it is important for the school to conduct supervision and education on healthy and wise mobile phone use among students.